2015
DOI: 10.4034/pboci.2015.151.29
|View full text |Cite
|
Sign up to set email alerts
|

Molar-Incisor Hypomineralization in Schoolchildren of São Luis, BrazilMaranhão: Prevalence and Associated Factors

Abstract: Objective: To determine the prevalence of molar-incisor hypomineralization (MIH) in the permanent dentition and assess the factors associated with these change in schoolchildren of São Luís, Brazil. Material and Methods: Overall, 1179 students aged 7-14 years of both sexes were included, all with permanent first molars and incisors erupted in the oral cavity. Oral clinical examination to assess the prevalence of HMI was held at school, under natural light. In the second stage, to assess factors associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…The characteristics of the 29 eligible studies are presented in Table . Fourteen were cross‐sectional studies, ten were case‐control studies and four were cohort studies . The number of patients included in the studies varied from 45 to 4049 children with a mean age of 9 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The characteristics of the 29 eligible studies are presented in Table . Fourteen were cross‐sectional studies, ten were case‐control studies and four were cohort studies . The number of patients included in the studies varied from 45 to 4049 children with a mean age of 9 years.…”
Section: Resultsmentioning
confidence: 99%
“…One study that was excluded presented a high risk of bias . Sixteen studies presented moderate risk of bias and 12 studies showed low risk of bias (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations